2022
DOI: 10.1177/09564624221127356
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and experiences of using oral voriconazole with or without concomitant topical agents to treat refractory vulvovaginal yeast infections

Abstract: Background We describe 11 cases of refractory vulvovaginal yeast infections (RVVYI) treated using oral voriconazole with or without concomitant topical agents. Methods Retrospective case-note review of all women prescribed oral voriconazole to treat RVVYI in five Sexual Health Clinics from Jan 2010-March 2020. Demographic details, clinical features, diagnostic results and treatment outcomes were collected. Results 11 women with vulvovaginal symptoms for a median of 1 year were treated with voriconazole. RVVYI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…One woman experienced tingling around the mouth after 5 days of treatment, which resolved within 24 h after taking the last dose of voriconazole. The study showed that voriconazole, alone or in combination with topical agents, may be effective in the treatment of refractory VVC [ 58 ].…”
Section: Treatment Of Complicated Vvcmentioning
confidence: 99%
“…One woman experienced tingling around the mouth after 5 days of treatment, which resolved within 24 h after taking the last dose of voriconazole. The study showed that voriconazole, alone or in combination with topical agents, may be effective in the treatment of refractory VVC [ 58 ].…”
Section: Treatment Of Complicated Vvcmentioning
confidence: 99%
“…6 Some studies have shown that voriconazole could be used as a salvage therapy for refractory fungal infections, including CM. [7][8][9] The successful use of voriconazole for the treatment of CM has only been reported in a few cases. [10][11][12] We conducted the current retrospective study to compare the efficacy and side effects of Voriconazole + 5-FC (Vori + 5-FC) and AmBd + 5-FC as induction treatments to determine whether Voriconazole-based therapy was superior to AmBd-based therapy in CM patients.…”
Section: Introductionmentioning
confidence: 99%
“…Voriconazole is a powerful antifungal drug against a broad spectrum of fungi, such as Aspergillus , Candida and Cryptococcus neoformans 6 . Some studies have shown that voriconazole could be used as a salvage therapy for refractory fungal infections, including CM 7–9 . The successful use of voriconazole for the treatment of CM has only been reported in a few cases 10–12 .…”
Section: Introductionmentioning
confidence: 99%